Energy Analysis of a Complementary Heating System Combining Solar Energy and Coal for a Rural Residential Building in Northwest China. (14th February 2018) - Zhen, Xiaofei; Li, Jinping; Abdalla Osman, Yassir Idris; Feng, Rong; Zhang, Xuemin; Kang, Jian
Abstract : In order to utilize solar energy to meet the heating demands of a rural residential building during the winter in the northwestern region of China, a hybrid heating system combining solar energy and coal was built. Multiple experiments to monitor its performance were conducted during the winter in 2014 and 2015. In this paper, we analyze the efficiency of the energy utilization of the system and describe a prototype model to determine the thermal efficiency of the coal stove in use. Multiple linear regression was adopted to present the dual function of multiple factors on the daily heat-collecting capacity of the solar water heater; the heat-loss coefficient of the storage tank was detected as well. The prototype model shows that the average thermal efficiency of the stove is 38%, which means that the energy input for the building is divided between the coal and solar energy, 39.5% and 60.5% energy, respectively. Additionally, the allocation of the radiation of solar energy projecting into the collecting area of the solar water heater was obtained which showed 49% loss with optics and 23% with the dissipation of heat, with only 28% being utilized effectively.